Acalypha wilkesiana flowers: Phenolic profiling, cytotoxic activity of their biosynthesized silver nanoparticles and molecular docking study for its constituents as Topoisomerase-I inhibitors. (July 2019) - El Raey, Mohamed A.; El-Hagrassi, Ali M.; Osman, Abeer F.; Darwish, Khaled M.; Emam, Mahmoud
Abstract: The bio potential behavior of green silver nanoparticles (AgNPs) using Acalypha wilkesiana flowers extract weas evaluated. The AgNPs formed were confirmed using surface plasmon resonance band showed in UV–vis spectrophotometer that characterized with spherical shape in size range from 5 to 45 nm depending on Transmission electron microscopy (TEM) and with good stability (−50.75 mV) depending on Zeta-potential measurements. In order to identify the capping agents responsible for the reduction of silver ion and the stabilization of nanoparticles prepared, Fourier transform-infrared spectroscopy (FTIR) and HPLC-ESI-MS analysis were used. Our AgNPs exhibited cytotoxic activity against MCF-7 (Breast carcinoma), PC-3 (Prostate carcinoma) and BJ-1 (skin normal human) cell lines with IC50 values 4.00, 3.6 and 4.1 μg/mL, respectively (i.e. the higher selectivity of AgNPs toward prostate than breast cancer cell lines was observed). These highly cytotoxic activity may be back to the presence of the bi-apigenin derivatives; amentoflavone and Cupressuflavone that displayed unique binding docking score towards the active site of human DNA topoisomerase enzyme. The present study is a distinctive application for the biosynthesis of silver nanoparticles in a fast, simple, easy, eco-friendly, inexpensive and effective way. Graphical abstract: The bio-synthesis of AgNPs using A. wilkesiana flower extract.Image 1 Highlights: The Ag + reduced to Ag o using plant extract without chemicals. The phytoconstituents of Acalypha wilkesiana were used as capping agents. LC–MS/MS analysis for A. wilkesiana extract has been studied in this work. The prepared green Ag NPs enhanced the cytotoxic activity. The molecular docking studies confirmed the activity of the identified metabolites toward Topoisomerase-I.